Islam, Media, dan Politik : Sebuah Perdebatan dan Kontempelasi Nilai Berdemokrasi - Idil Akbar (Department of Government Studies Universitas Muhammadiyah Makassar, 2016)
Infact, press or media is one of pilar democracy. Media in democracy is a public sphere to communi-cation and makes relation, and a same time as public arena to gain information. But, media also could not release from streotypes and tendency that usually bring of interest, either the owner or ideology. It is meaning media can not released from perspective distorsion, values bias and take a side. Media also effective to become propaganda instrument for a political interest and an ideology. It is seen like how media in US, for example, stereotype of Islam in discourses contradiction and glob-al interest opposition. Then, Islam dominantly identified as doctrine teaches radicalism, fundamen-talism and terorism. Thus, it is often be justification for US to operate the military mission in the name of democracy.Tak dipungkiri pers atau media menjadi salah satu pilar bagi demokrasi. Media dalam demokrasi adalah sebagai ruang bagi publik berkomunikasi dan berinteraksi, sekaligus sarana publik mem-peroleh informasi tentang banyak hal. Namun, media juga tak bisa dilepaskan dari stereotip dan kecenderungan-kecenderungan, yang biasanya membawa kepentingan, baik pemilik maupun ide-ologi. Media karenanya tak lepas dari distorsi perspektif, bias nilai dan berpihak. Media juga efektif menjadi alat propaganda bagi sebuah kepentingan politik dan ideologi, seperti bagaimana media di negara Amerika, misalnya, menstereotipkan Islam dalam analisis pertentangan wacana dan kepent-ingan global. Sehingga, dominan Islam diidentikkan dengan sematan sebagai ajaran yang mengajarkan radikalisme, fundamentalisme dan terorisme. Karenanya pula seringkali menjadi alasan pembenar bagi Amerika untuk menjalankan misi militer atas nama demokrasi.